The composition of the oil of starfruit (Averrhoa carambola, Linn.) seeds - Berry, Shiv K. (Wiley, 1978)
The starfruit (Averrhoa carambola, Linn.) seeds were found rich in oil. The oil was examined for its refractive index, iodine value, acid value, saponification number, unsaponifiable matter, and fatty acid composition by gas liquid chromatography. The values (area percent) for fatty acids as methyl esters were: C14:0 (0.67%); C16:0 (21.34%); C18:0 and C24:0 (trace).